Understanding Thermal and A‐Thermal Trapping Processes in Lead Halide Perovskites Towards Effective Radiation Detection Schemes. (30th July 2021) - Rodà, Carmelita; Fasoli, Mauro; Zaffalon, Matteo L.; Cova, Francesca; Pinchetti, Valerio; Shamsi, Javad; Abdelhady, Ahmed L.; Imran, Muhammad; Meinardi, Francesco; Manna, Liberato; Vedda, Anna; Brovelli, Sergio
Abstract: Lead halide perovskites (LHP) are rapidly emerging as efficient, low‐cost, solution‐processable scintillators for radiation detection. Carrier trapping is arguably the most critical limitation to the scintillation performance. Nonetheless, no clear picture of the trapping and detrapping mechanisms to/from shallow and deep trap states involved in the scintillation process has been reported to date, as well as on the role of the material dimensionality. Here, this issue is addressed by performing, for the first time, a comprehensive study using radioluminescence and photoluminescence measurements side‐by‐side to thermally‐stimulated luminescence (TSL) and afterglow experiments on CsPbBr3 with increasing dimensionality, namely nanocubes, nanowires, nanosheets, and bulk crystals. All systems are found to be affected by shallow defects resulting in delayed intragap emission following detrapping via a‐thermal tunneling. TSL further reveals the existence of additional temperature‐activated detrapping pathways from deeper trap states, whose effect grows with the material dimensionality, becoming the dominant process in bulk crystals. These results highlight that, compared to massive solids where the suppression of both deep and shallow defects is critical, low dimensional nanostructures are more promising active materials for LHP scintillators, provided that their integration in functional devices meets efficient surface engineering. Abstract : Lead halide perovskites are emerging as active materials for radiation detection. Through complementary spectroscopies, the carrier trapping/detrapping mechanisms affecting the scintillation performance of CsPbBr3 with increasing dimensionality, from nanocubes to nanowires, nanosheets, and bulk crystals, are elucidated. The nanostructures are dominated by slow detrapping via a‐thermal tunneling from shallow defects, whereas bulk crystals show a further thermal detrapping contribution.